Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1149/1.2759841
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Intercalation of Fluoride-Anion Receptor Complexes in Graphite

Abstract: We have demonstrated a route to reversibly intercalate fluoride-anion receptor complexes in graphite via a nonaqueous electrochemical process. This approach may find application for a rechargeable lithium-fluoride dual-ion intercalating battery with high specific energy. The cell chemistry presented here uses graphite cathodes with LiF dissolved in a nonaqueous solvent through the aid of anion receptors. Cells have been demonstrated with reversible cathode specific capacity of approximately 80 mAh/g at dischar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 25 publications
(30 reference statements)
2
62
0
Order By: Relevance
“…780 More recently, West et al used a series of anion-receptors based on fluoroalkylborates or -boronates to form complex anions with fluoride (F − ) and showed that anions of such sizes could still electrochemically intercalate into graphite at ∼5.0 V in PC, accompanied by an expansion in interlayer distance between graphene sheets to ∼0.99 nm. 781 Although the process was still demonstrated in a cathode half cell, decent reversibility was obtained in this case as compared to previous studies. Realizing that most of the electrolyte solvents cannot satisfy interphasial chemistry requirements at graphitic anodes and graphitic cathodes simultaneously, Placke et al replaced the graphitic anode with another intercalation host, Li 4 Ti 5 O 12 , which operates at 1.5 V and does not require SEI formation.…”
Section: Dual-intercalation Chemistrysupporting
confidence: 49%
“…780 More recently, West et al used a series of anion-receptors based on fluoroalkylborates or -boronates to form complex anions with fluoride (F − ) and showed that anions of such sizes could still electrochemically intercalate into graphite at ∼5.0 V in PC, accompanied by an expansion in interlayer distance between graphene sheets to ∼0.99 nm. 781 Although the process was still demonstrated in a cathode half cell, decent reversibility was obtained in this case as compared to previous studies. Realizing that most of the electrolyte solvents cannot satisfy interphasial chemistry requirements at graphitic anodes and graphitic cathodes simultaneously, Placke et al replaced the graphitic anode with another intercalation host, Li 4 Ti 5 O 12 , which operates at 1.5 V and does not require SEI formation.…”
Section: Dual-intercalation Chemistrysupporting
confidence: 49%
“…However, even in the early days of anion receptor research, researchers found other uses of these interesting molecules. To begin with, anion receptors can greatly increase the solubility of salts that are otherwise almost insoluble in organic electrolytes, such as LiF [70,119,138], Li 2 O, and Li 2 O 2 ( Fig. 10) [150].…”
Section: Ion Receptorsmentioning
confidence: 99%
“…Electrolytes based on these salts that are traditionally For example, the fluoride anion can be reversibly intercalated into graphite through a soluble fluoride-anion-receptor complex, making graphite as a cathode material. Based on this finding, a dual graphite intercalating cell with discharge voltage over 4.8 V has been realized [138]. Furthermore, anion receptors have been known to stabilize the metallic lithium anode in lithium metal batteries [31,173].…”
Section: Ion Receptorsmentioning
confidence: 99%
“…However, the relative insolubility of the LiF in many nonaqueous electrolyte solvents limits its use as a viable electrolyte salt, and therefore the use of the fluoride specific anion receptors as electrolyte additives is a clear alternative towards achieving enhanced solubility of LiF and thereby the relatively increased lithium ion transference numbers. [5][6][7][8][9][10][11] The selective reversible binding of these boron-based anion receptors resulted in The use of these anion recepors allows the use of LiF as a low molecular weight electrolyte in the lithium ion batteries. Whereas LiF is essentially insoluble in the nonaqueous electrolyte solvents such as dimethyl ether (DME) and carbonate based solvents, in the presence of anion receptors LiF is relatively highly soluble, and typically 1 M solutions of LiF in dimethyl ether could be obtained so that high lithium ion conductivities could be achieved in lithium ion batteries.…”
Section: Introductionmentioning
confidence: 99%
“…Amine and coworkers' ab initio calculations, for example, show that the M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 5 5 fluoride anion affinity is reduced by the introduction of the alkoxyl groups on the boron center and that the fluoride anion affinity increases with the substitution of the electron-withdrawing groups on the boron (e.g., fluoroalkyl or fluoroaryl aryl substitutents on the boron). 26 The anion receptor TPFPB was shown also to complex with PF 6 -anion (i.e., in addition to its complexation with the fluoride anion) so that the lithium ion transference number (and thereby the ionic conductivity) of the cells consisting of LiPF 6 electrolyte are significantly increased. 27 the NH bond of the urea deivative is successively, almost completely deprotonated upon addition of the tetrabutylammonium fluoride.…”
Section: Introductionmentioning
confidence: 99%